ナンキョク サン ムカデゴケ ゾク チイ ノ 2シュ - 中西, 哲; ナカニシ, サトシ; 柏谷, 博之; カシワダニ, ヒロユキ; NAKANISHI, Satoshi; KASHIWADANI, Hiroyuki (国立極地研究所, 1976)
P(論文) 生物担当の夏隊員として,第16次南極地域観測に従事した中西は1975年1月中旬から2月上旬にかけて,宗谷海岸やプリンスオラフ沿岸の露岩地でコケ類,地衣類の調査を行った.この時に採集した地衣類標本の中に成熟した子器をつけたムカデゴケ属の1標本のあるのを発見した.筆者らの一人柏谷がそれを検討した結果,それは日本,ヨーロッパ,北米から知られているコフキシロムカデゴケ(Physcia caesia (HOFFM.) HAMPE)であることが判明した.南極でこの種の子器が発見されたのははじめてである.また,南極地域から未報告のPhyscia dubia (HOFFM.) LETT.を採集していることもわかった. Under the project of JARE-16, the senior author made field works in the ice-free areas of Soya Coast and Prince Olav Coast, Antarctica in January-February of 1975. Among the lichens collected, we found a specimen of Physcia caesia (HOFFM.) HAMPE with developed apothecia, though fertile specimen had never been collected before in Antarctica. The morphology of apothecia and spores of the Antarctic specimen is quite identical with that of P. caesia collected in Japan as well as in Europe and North America. Among his collection, we also found four specimens of Physcia dubia (HOFFM.) LETT., which had not been reported from Antarctica. departmental bulletin paper